Italian nonsense verse: rewriting poetry in Alice’s Adventures in Wonderland by Lewis Carroll translated into Italian - Alborghetti, Claudia (Rivista di Storia dell’Educazione, 2020)
Alice’s Adventures in Wonderland (1865) was translated in Italy for the first time in 1872 by Teodorico Pietrocòla Rossetti. Since then, it has found fruitful ground in the so-called “creative transposition” (Jakobson, 2002), which makes use of the creative channel to communicate with a lay public that relies on rewritings to approach classic texts (Lefevere, 1992). Rewriters include translators and people who manipulate source texts for economic, political or social reasons. Their work is evidence of the evolution of literature as it brings classic texts down to the level of the common reader, ensuring their survival through time. Alice, a mixture of narrative voice and nonsense poetry, survives through the rewritings aimed at a young public. This paper explores poetry in selected translations of Alice’s Adventures in Wonderland, including Donatella Ziliotto’s translation published by Salani in 2010, Masolino D’Amico’s translation in the children’s literature series of classics published by BUR Ragazzi in 2016, and the modernized re-edition of Silvio Spaventa Filippi’s translation first published in 1913, distributed in a new book series in 2013. The translations analysed have all been published between 1991 and 2016 by different translators and publishing houses. This selection allowed for a mixed methodology of analysis delving into the paratext and poetic language, in order to compare rhythm, structure and rhyme, looking for common aspects but especially divergent approaches as a mark of creativity wishing to release the potential of the poetic verse and mediate it for young readers.